A cross‐temporal meta‐analysis review of the personality of Chinese military personnel, 1991–2017. (6th December 2020) - Su, Qian; Liu, Guofang
Abstract: Objective: The personality of military personnel is an important factor for their mental health. It has been revealed that military personnel's mental health has changed over the past decades. The objective of the present study was to examine the birth cohort changes in the personality of Chinese military personnel. Methods: To examine the birth cohort changes in the personality of Chinese military personnel, a cross‐temporal meta‐analysis of 53 studies that measured the personality of Chinese military personnel with the Eysenck Personality Questionnaire from 1991 to 2017 was conducted (61 data points, N  = 55 708). Results: The results showed that during this period, the respondents' personality traits changed significantly. Specifically, their levels of neuroticism and psychoticism decreased by 0.84 and 0.62 standard deviations respectively, and the younger participants exhibited higher levels of extraversion. Conclusions: This study found that Chinese military personnel showed decreasing neuroticism and psychoticism from 1991 to 2017 and that younger participants exhibited higher levels of extraversion. © 2020 John Wiley & Sons, Ltd.